Research on the Construction of Indonesian Chinese Language Acquisition Case Resource Based on Building Learning Communities - Wei, Yangyang (Journal of Chinese Language and Culture Studies, 2024)
Acquisition case resources, as integrated accounts of experiences from Chinese learners, serve as high-quality resources for Indonesians to understand Chinese language and culture, thereby contributing to the construction of a local Chinese language learning community in Indonesia. Ultimately, they inject new vitality and momentum into the co-construction of the "China-Indonesia Community of Shared Future." This paper aims to explore the general principles, needs analysis, overall approach, and development path of constructing an Indonesian Chinese language acquisition case resource library. Finally, it proposes the role and significance of case resources in teaching and research. The construction of Chinese language acquisition case resources will provide new insights and support for the localization of international Chinese education in Indonesia.